Effects of Inhaled Nitric Oxide on Oxidative Stress and Histopathological and Inflammatory Lung Injury in a Saline-Lavaged Rabbit Model of Acute Lung Injury - Fioretto, José Roberto [UNESP]; Campos, Fabio J.; Ronchi, Carlos F. [UNESP]; Ferreira, Ana Lúcia dos Anjos [UNESP]; Kurokawa, Cilmery Suemi [UNESP]; Carpi, Mario Ferreira [UNESP]; Moraes, Marcos A. [UNESP]; Bonatto, Rossano César [UNESP]; Faveri, Julio de [UNESP]; Yeum, Kyung-Jin (Daedalus Enterprises Inc, 2012)
BACKGROUND: Conventional mechanical ventilation (CMV) is fundamental in acute respiratory distress syndrome (ARDS) treatment. Inhaled nitric oxide (INO), an adjunctive therapy, has been used with ventilation in an attempt to improve oxygenation and reduce lung injury. OBJECTIVE: To analyze the early effects of low INO dose on oxygenation, oxidative stress, inflammatory, and histopathological lung injury in a rabbit model of acute lung injury (ALI). METHODS: This was a prospective, controlled, in vivo animal laboratory study. Forty rabbits were instrumented and ventilated at F-IO2 1.0. ALI was induced by tracheal infusion of warm saline (30 mL/kg, 38 degrees C) and lung oxidative stress was assessed by total antioxidant performance (TAP) assay. Animals were assigned to groups: control group (no. = 10, low tidal volume [V-T] = 6 mL/kg, PEEP = 5 cm 1120), ALI without INO (no-INO group, no. = 10, low V-T = 6 mL/kg, PEEP = 10 cm H2O), ALI plus INO (INO group, no. = 10, low V-T = 6 mL/kg, PEEP = 10 cm H2O, INO = 5 ppm). Plateau pressure was limited to 30 cm H2O in all groups. Ten non-instrumented animals (healthy group) were studied for TAP assay. Ventilatory and hemodynamic parameters were recorded every 30 min for 4 hours. RESULTS: After lung injury, the instrumented groups were worse than the control group for P-aO2 (control group 438 +/- 87 mm Hg, no-INO group 80 +/- 13 mm Hg, INO group 81 +/- 24 mm Hg, P < .001). The INO group showed decreased lung inflammation by leukocyte count in lung lavage fluid (no-INO group 4.8 +/- 1.64, control group 0.16 +/- 0.15, INO group 0.96 +/- 0.35 polymorphonuclear cells x 10(6)/bronchoalveolar lavage fluid/lung, P < .001), decreased histopathological injury score (no-INO group 5 [range 1-16], INO group 2 [range 0-5], control group 0 [range 0-3], P < .001), and better lung protection against oxidative injury than the no-INO group (healthy group 68 +/- 8.7, control group 66.4 +/- 6.8, INO group 56.3 +/- 5.1, no-INO group 45.9 +/- 3.4 percent protection/g protein, P < .001). CONCLUSIONS: INO attenuates oxidative stress and histopathological and inflammatory lung injury in a saline-lavaged rabbit ALI model.
Keywords: ARDS; mechanical ventilation; oxidative injury; acute lung injury; rabbits; inhaled nitric oxide